Impact of lesson study on mathematics lecturers’ content knowledge and pedagogical content knowledge and students’ problem solving ability, motivation and anxiety - Gholami, Hosseinali (2020)
Mathematics lecturers who are teaching at the foundation level, which is one of the pre-university programmes in Malaysia, play an essential role in preparing students for higher-level mathematics or courses that extend mathematics knowledge beyond what was covered in secondary school. A lecturer with a limited grasp of mathematical content knowledge and pedagogical content knowledge has little room for progress or novelty in the classroom or the ability to fuel students’ interest in the mathematics subject. The results of international assessments in mathematics showed that students in countries such as Singapore and Japan are very successful in mathematics at the school level. This indicates that the students have high potential in their ability to do problem solving and higher order thinking when they pursue mathematics learning in higher education. In these countries, mathematics teachers work together and research about lesson plans collaboratively. They improve their content knowledge and pedagogical content knowledge through teamwork using a method of mathematics teaching which originated from Japan, which is called Lesson Study. This study was conducted in a Foundation Center of a public university in Malaysia. The study which employed the mixed method was aimed to explore the impact of Lesson Study on mathematics lecturers’ content knowledge (common content knowledge and specialized content knowledge) and pedagogical content knowledge (knowledge of content and teaching as well as knowledge of content and students) and students’ outcomes in mathematical problem solving, motivation in mathematics and mathematics anxiety. A group of nine lecturers (seven mathematics lecturers, a physic lecturer and the researcher) contributed in developing research lessons through Lesson Study and two foundation classes with 95 students participated in the experimental part of the study. The researcher adopted the qualitative case study method to understudy the Lesson Study group and quasiexperimental method for the two foundation classes which were assigned as control and experimental groups. The lecturers collaboratively planned, discussed and designed five research lessons and following that, the students underwent five weeks of learning based on the lessons developed. Data collection methods which comprised of interviews, observations and mathematics tests were used to collect data of the lecturers. Data for the quantitative part were collected using tests to determine the students’ mathematical problem solving ability, as well as a motivation questionnaire (Butler, 2016) and an anxiety questionnaire (Bai, 2011). The results of this study showed that mathematics lecturers through collaborative work and sharing of knowledge and experiences greatly improved their content knowledge and pedagogical content knowledge. Furthermore, there were significant differences between the experimental and control groups in scores for mathematics problem solving tests, motivation and anxiety but there is no statistical significant interaction between treatment groups and gender on problem solving tests, motivation and anxiety scores. In summary, the results of this study showed that Lesson Study is a dynamic teaching method for pre-university programme and it has potentials in improving mathematics lecturers’ content knowledge (common content knowledge and specialized content knowledge) and pedagogical content knowledge (knowledge of content and teaching as well as knowledge of content and students) in order to enhance student learning in mathematics through use of research lessons based on problem solving approach and higher order thinking skills.